1989
DOI: 10.1111/j.1348-0421.1989.tb01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Small Round Structured Virus Infections in Acute Gastroenteritis Outbreaks in Tokyo

Abstract: During the three-year period from 1984 to 1987, 506 acute gastroenteritis outbreaks involving 14,383 patients were reported to the Bureau of Public Health, Tokyo Metropolitan Government. Eighty (4,324 patients) of 150 outbreaks (4,860 patients) from which etiologic agents were not identified were subjected to virological investigation. Spherical particles of 28-32 nm in diameter with capsomere-like structures on the surface were detected in patients' stool specimens. Buoyant density of the particles appeared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 14 publications
(14 reference statements)
1
19
0
1
Order By: Relevance
“…Foodborne infections by SRSV have been reported in winter in Japan [Hayashi et al, 1991;Oishi et al, 1992;Sekine et al, 1989;Taniguchi et al, 1979]. OTH-25/89/J-like and SMA/76/US-like viruses were detected as the causative agents in some cases.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Foodborne infections by SRSV have been reported in winter in Japan [Hayashi et al, 1991;Oishi et al, 1992;Sekine et al, 1989;Taniguchi et al, 1979]. OTH-25/89/J-like and SMA/76/US-like viruses were detected as the causative agents in some cases.…”
Section: Resultsmentioning
confidence: 96%
“…Small round structured viruses (SRSV) are causative agents of airborne, foodborne, and waterborne outbreaks of vomiting and acute gastroenteritis [Kaplan et al, 1982;Morse et al, 1986;Sawyer et al, 1988;Sekine et al, 1989] in children and adults. SRSVs are often transmitted from person to person in hotels, restaurants, and public houses [McDonnell et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of foodborne NLV transmission vary from 68% 30 at one extreme to 7.6% 31 at the other. Given its high incidence it is important to use an accurate figure for percentage foodborne transmission.…”
Section: Estimating the Number Of Cases Of Foodborne Infectionmentioning
confidence: 99%
“…In Japan, small round virus infections have been reported in several oyster-associated gastroenteritis outbreaks [7]. It has been suggested that bacteriological indicators such as standard plate counts and coliform indices may be poor indicators of the level of viral contamination [3,8,9].…”
Section: Introductionmentioning
confidence: 99%